Postconcussive Syndrome Following Sports-related Concussion. Issue 9 (September 2015) - Moran, Byron; Tadikonda, Prathima; Sneed, Kevin B.; Hummel, Michelle; Guiteau, Sergio; Coris, Eric E.
<x xml:space="preserve">Abstract</x> Abstract Postconcussive syndrome is an increasingly recognized outcome of sports-related concussion (SRC), characterized by a constellation of poorly defined symptoms. Treatment of PCS is significantly different from that of SRC alone. Primary care physicians often are the first to evaluate these patients, but some are unfamiliar with the available therapeutic approaches. This review provides an overview of the pathophysiology of SRC and descriptions of both pharmacologic and nonpharmacologic treatment options to allow primary care physicians to provide evidence-based care to patients experiencing postconcussive syndrome.